Characterisation of a thermotolerant yeast, Kluyveromyces marxianus CBS712 - Erdei, Éva; Molnár, Mónika; Gyémánt, Gyöngyi; Harangi, János; Nagy, János; Pócsi, István (Acta Agraria Debreceniensis, 2009)
Fermentation at high temperature with application of thermotolerant microorganisms is a technological advantage in bioethanol production. Among the yeasts, K. marxianus has outstanding thermotolarance. The industrial application of the IMB3 strain occurs usually at 45C. The final aim of our project is the genetic modification of the K. marxianus CBS712 strain in order to achieve ethanol production at higher temperature than the currently applied. This requires the characterization of the CBS712 strain, with special attention to the determination of the temperature limit of its growth and the amount of the ethanol produced. The temperature limit of growth was 48C in YPD medium. Elevation of the temperature above 45C led to an exponential drop of the cell viability. Ethanol production was tested in shaking flasks, in MYFM medium, under oxigene limited conditions, applying variable concentrations of glucose (12–20%) and different temperatures (45–47 ºC). Preliminary results have revealed that the elevation of glucose concentration increased the amount of ethanol produced. The amount of ethanol (appr. 5%)+ produced at the highest glucose concentration was not different at the tested temperatures (45, 46 and 47 ºC). The observation indicates the potential in raising the thermotolerance of the strain.